Creative Communication as a Catalyst for Change: Shaping Urban Development Through Psychology and Art - Razali, Geofakta; Mutma, Fasya Syifa; Adriana, Nadya Puspita; Angelina, Donna; Saldi, Zaki Saptari (Communica : Journal of Communication, 2023)
This research discusses the role of creative communication in Indonesia as a catalyst in the formation and development of urban areas. Adopting an interdisciplinary approach that integrates psychology, art, and communication, this study reveals the dynamics between creativity and urban development. Firstly, the research explores the influence of creative design in urban spaces on community psychology and behavior, including the effects of color, shape, and other visual elements. Secondly, a case analysis of art installations and interactive media in public spaces highlights their role as communication tools that enrich urban experiences. Thirdly, the research emphasizes innovation in urban planning that combines creative design and advanced technology. Fourthly, this analysis includes the impact of digital media and social platforms on urban perception, covering the use of social media in urban campaigns. Lastly, the study underscores the importance of community engagement through art and creativity in city development. This research provides evidence that well-designed urban environments can enhance mental health and social well-being.